FINITE-ELEMENT MODELING OF SALT TECTONICS - Bakhova, Natalia (Proceedings of National Aviation University (archive), 2012)
The two-dimensional thermal model of graben structure in the presence of salt tectonics on the basis of a finite elements method is constructed. The analysis of the thermal field is based on the solution of stationary equation of heat conductivity with variable boundary conditions. The high precision of temperatures distribution and heat flows is received. The decision accuracy is no more than 0,6 %.